From Room to Tomb: Moonlight - Dilek Inan (ELOPE, 2012)
In 1993, a decade of directly political plays was followed by Moonlight, which in the Guardian’s words would “come as a shock to those who have lately pigeonholed Harold Pinter as a writer of bruising polemic” (Billington 1993, 1). Although Moonlight made history as Pinter’s first full length work for the theatre since Betrayal, it should rather be seen as an interval from politics where the playwright re-explores the interior landscapes of his early work, where he returns to the pastoral as a landscape of retreat and fantasy. Indeed, the play’s title suggests a pastoral realm. The heroine retreats into Nature through linguistic idealisation. Moonlight can best be comprehended as Pinter briefly leaving politics to explore new horizons – “his own private griefs and anguish in the most nakedly and unashamedly emotional of all his plays” (Billington 1996, 338). This paper evaluates Moonlight as a reworking of Pinter’s own roots thematically, stylistically and spatially.